Destination Image as a Mediator of the Influence of Service Quality on the Decision to Purchase Dolphin Tourism Services - Komang Endrawan Sumadi PUTRA; Made Putri ARIASIH (International Journal of Environmental, Sustainability, and Social Science, 2024)
This study examines the role of destination image in mediating the impact of service quality on tourists' purchasing decisions for Dolphin tour packages at Lovina Beach, North Bali. Fluctuations in tourist visits from 2019 to 2022 have affected the Dolphin Tour business, with poor service quality discouraging potential customers. This research employs a quantitative approach using purposive sampling, with 150 respondents who purchased Dolphin tour packages. Data collection was conducted through direct questionnaires, and analysis was performed using Structural Equation Modeling (SEM) with Partial Least Squares (PLS) via Smart PLS 3.0. The results indicate a significant direct and indirect effect of service quality on purchasing decisions through destination image. This suggests that improving service quality enhances the destination image, ultimately increasing tourist interest in purchasing Dolphin tour packages. The findings highlight the need for Dolphin tourism service providers to enhance service quality to attract more visitors and sustain the industry.